Riflessioni ed ipotesi di ri/territorializzazione ecologica - Stefano Aragona (ArcHistoR Architettura Storia Restauro: Architecture History Restoration, 2020)
The paper highlights how the small and very small centres, equal to 69.9% of the Italian Municipalities, the connective tissue of the “Country of the 100 Bell Towers” built over millennia, suffer abandonment processes. Insane policies of cuts in connections along with those of privatization and liberalization are among the main culprits in the disappearance of the historical landmarks of the territory. While the main poles are enjoying high speed and special funding with the EU Urban Agenda. To reverse this situation, having as a reference the Landscape Charter, for years an integrated ecological approach has been proposed based on the indications of the Leipzig Charter which calls for integrated strategies for bread-making between rural and urban, small, medium, large and metropolitan areas. It is examined the National Strategy for Inland Areas, launched in 2013, to assess the quality of life of the citizens of these areas and the law, issued in 2017, in support of the Municipalities under the 5000 inhabitants is considered. They are an opportunity to modify the settlement logic that developed over more than 300 years based on the industrialist paradigm that is increasingly showing environmental and social unsustainability. Then at the center is placed the cum-cives, that is the citizen, who with the others shares the civitas to build inclusive and sustainable communities materially and socially, the goal of Smart City.